VANCOMYCIN INTERMEDIATE AND VANCOMYCIN RESISTANT STAPHYLOCOCCUS AUREUS – MECHANISMS, CLINICAL SIGNIFICANCE AND DETECTION - Kumari, Jyoti; SHALINI SHENOY M; Hegde, Ashwini; K, Vidyalakshmi; M, Chakrapani; Bhat k, Gopalkrishna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Vancomycin is used as the antibiotic of choice for severe infection caused by methicillin resistant Staphylococcus aureus. Increased use of vancomycin and the selective pressure has resulted in the emergence of S.aureus with reduced susceptibility to vancomycin and vancomycin resistant S.aureus. This review summarizes the definition, mechanism, clinical significance and epidemiology of S.aureus with reduced susceptibility to vancomycin. It also discusses laboratory methods for detection and treatment options available for these pathogens.